Фотосинтетическая продуктивность интенсивных насаждений яблони при микроорошении - Козлова, Лилия Валентиновна; Козлова, Лілія Валентинівна; Kozlova, Liliia (My University, 2013)
RU: Представлены результаты исследований о влиянии водного режима почвы на чистую продуктивность фотосинтеза интенсивных насаждений яблони при разных схемах посадки. Выявлено, что режим орошения был доминирующим фактором, который существенно повлиял на величину ЧПФ. При схеме посадки деревьев яблони 4х1,5 м этот показатель был больше, чем при схеме посадки 4х1 м. Наибольшая величина ЧПФ отмечена на варианте с назначением поливов расчетным методом при 110% (Е0 – О) у сорта Флорина по сравнению с сортами Айдаред и Голден Делишес. Установлена прямая зависимость между водопотреблением деревьев яблони и чистой продуктивностью фотосинтеза. EN: The results of the research about influence of soil water regime upon pure productivity of photosynthesis of intensive apple orchards with different schemes of planting are given. It was found out that irrigation regime was the dominant factor that determined the amount of pure productivity of photosynthesis. This index was higher for scheme of planting 4x1.5 meter than for 4x1 meter. The biggest amount of pure productivity of photosynthesis was observed for the variant with irrigation determination by calculation method with 110% (Е0 – О) for Florina variety compared to varieties Idared and Golden Delicious. Direct relationship between water consumption of trees and pure productivity of photosynthesis was found out.
Photosynthetic productivity of intensive apple orchards with microirrigation
Keywords: яблоня; режим орошения; чистая продуктивность фотосинтеза; схема посадки; сорт; irrigation regime; apple; pure productivity of photosynthesis; scheme of planting; variety